The Kalkarindji Large Igneous Province, Australia: Petrogenesis of the oldest and most compositionally homogenous province of the Phanerozoic - Ware, Bryant; Jourdan, Fred; Merle, Renaud; Chiaradia, M.; Hodges, K. (Oxford University Press, 2018)
The Kalkarindji Large Igneous Province (LIP) is a Middle Cambrian (511 Ma) continental flood basalt (CFB) province located in northern and central-west Australia that has been linked to an extinction event at the Early-Middle Cambrian boundary. The extent of this LIP has been estimated at about 2.1 × 106km2, with exposures in Western Australia, Northern Territory, Queensland and South Australia. Major and trace element datasets reveal geochemical characteristics typical for continental flood basalts (CFBs) including: tholeiitic affinity; an enrichment in incompatible elements, in particular, large-ion lithophile elements (LILE); enrichment of light rare earth elements (LREE) compared to heavy rare earth elements (HREE) relative to N-MORB; negative Nb and Ta anomalies in normalized extended element patterns. Here we present the first comprehensive geochemical investigation of the Kalkarindji CFB province. The Kalkarindji CFBs are geochemically homogeneous, low-Ti basaltic andesites, with a nearly complete lack of basalts as defined using a total-alkalis vs silica diagram. All of the rocks analysed for Sr, Nd, Pb isotopic ratios display enriched initial (t=511 Ma) isotopic compositions (143Nd/144Ni=0.511928- 0.511981;87Sr/86Sri=0.70917-0.71029;206Pb/204Pbi=18.105-18.843;207Pb/204Pbi=15.726-15.805;208Pb/204Pbi=38.374-39.208). Crustal assimilation models are interpreted to suggest that the geochemical characteristics, as well as the homogenous composition across the entire province, cannot be explained by continental crust contamination. Therefore, the enriched isotopic ratios (particularly the extremely high207Pb/204Pbi and elevated208Pb/204Pbi for moderate206Pb/204Pbi), coupled with relative depletions in Nb and Ta concentrations, indicate the involvement of an ancient enriched lithospheric-like component in the genesis of the Kalkarindji CFB. We propose a model in which the source region was affected by an enrichment event at around 2.5 Ga (possibly through the addition of subducted sediments). Decompression melting and mantle warming (focused by edge driven convection) allowed melting of the fertile mantle to generate the Kalkarindji CFB province at c. 511 Ma.